2012
DOI: 10.1037/a0027267
|View full text |Cite
|
Sign up to set email alerts
|

Relationship satisfaction and depressive symptoms in emerging adults: Cross-sectional associations and moderating effects of relationship characteristics.

Abstract: Extending research that was based on married adults, we explored associations between romantic relationship satisfaction and depressive symptoms in a sample of 484 emerging adults (ages 18-25) in nonmarital dating relationships. In addition, we investigated whether the relationship characteristics of relationship length, interdependence (i.e., investment size and quality of alternatives) and commitment moderated these associations. Overall, there was a negative association between relationship quality and depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
76
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 52 publications
9
76
0
1
Order By: Relevance
“…Because interpersonal relations are, 5 on average, more central to women's than men's identities and self-concepts, 11 romantic relationships are theorized to be more strongly associated with women's than men's mental health. Both depressive symptoms and general psychological distress are more strongly associated with marital satisfaction 12,13 and college dating relationship satisfaction 14 for women than for men. Most previous studies of ADHD and relationship functioning have either examined samples of one gender 6,9 or have not examined gender differences.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Because interpersonal relations are, 5 on average, more central to women's than men's identities and self-concepts, 11 romantic relationships are theorized to be more strongly associated with women's than men's mental health. Both depressive symptoms and general psychological distress are more strongly associated with marital satisfaction 12,13 and college dating relationship satisfaction 14 for women than for men. Most previous studies of ADHD and relationship functioning have either examined samples of one gender 6,9 or have not examined gender differences.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…For this study, we used attachment theory to understand the influence of past relationships, self-efficacy to understand individual cognition about romantic relationships, and relational anxiety to understand about individual emotional responsivity and, consequently, how these relational antecedents associate with well-being. Although romantic relationships in college may be transient, data find that successful relationships can support overall well-being and happiness (Braithwaite, Delevi, & Fincham, 2010;Ratelle, Simard, & Guay, 2013;Whitton & Kuryluk, 2012).…”
Section: Introductionmentioning
confidence: 93%
“…For example, Mellor et al (2008) found that satisfaction with personal relationships was moderately and negatively correlated with loneliness. In turn, Whitton and Kuryluk (2012) found a negative correlation between satisfaction in dating relationships and depressive symptoms, and Levis et al (2015) found in their study that women in poorquality marriages reported worse mental health compared to unmarried women. As a result, increased status satisfaction would be expected to be associated with decreased romantic loneliness.…”
Section: Introductionmentioning
confidence: 99%